"Every Kid Is Money": Market-Like Competition and School Leader Strategies in New Orleans. (December 2015) - Jabbar, Huriya
One of the primary aims of choice policies is to introduce competition between schools. When parents can choose where to send their children, there is pressure on schools to improve to attract and retain students. However, do school leaders recognize market pressures? What strategies do they use in response? This study examines how choice creates school-level actions using qualitative data from 30 schools in New Orleans. Findings suggest that school leaders did experience market pressures, yet their responses to such pressures varied, depending in part on their perceptions of competition and their status in the market hierarchy. Some took steps toward school improvement, by making academic and operational changes, whereas others engaged in marketing or cream skimming.